2010
DOI: 10.1107/s0021889810004759
|View full text |Cite
|
Sign up to set email alerts
|

Photocrystallography – design and methodology for the use of a light-emitting diode device

Abstract: With the increase in interest in photocrystallographic experiments, the use of light‐emitting diodes (LEDs) provides an alternative, low‐budget light source (by comparison to lasers) and allows photocrystallographic experiments to be carried out readily. Here the design of an LED array device suitable for use in single‐crystal X‐ray diffraction experiments is reported, and the experimental methodology used for determining the structures of metastable species is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…For photocrystallographic studies, the X-ray set-up described above was modified to incorporate a purpose-built LED ring array, 21 positioning five LEDs (400 nm: Bivar UV5TZ-400-15, λ p = 400 ± 2.5 nm, 3.4 V, 15 mA, 40 mW) at a distance of approximately 1 cm from the crystal in a uniform arc. This setup ensures even irradiation on all sides of the crystal, and enables the collection of complete single-crystal X-ray data while the array remains in place.…”
Section: In Situ Photocrystallographymentioning
confidence: 99%
“…For photocrystallographic studies, the X-ray set-up described above was modified to incorporate a purpose-built LED ring array, 21 positioning five LEDs (400 nm: Bivar UV5TZ-400-15, λ p = 400 ± 2.5 nm, 3.4 V, 15 mA, 40 mW) at a distance of approximately 1 cm from the crystal in a uniform arc. This setup ensures even irradiation on all sides of the crystal, and enables the collection of complete single-crystal X-ray data while the array remains in place.…”
Section: In Situ Photocrystallographymentioning
confidence: 99%
“…The crystal was then irradiated with 400 nm LED light at 100 K for a period of 1 h, in-situ on the diffractometer using a specifically designed LED ring array. This experimental set up has been described previously 16 and positions six LEDs in a ring c.a. 1 cm from the crystal position.…”
mentioning
confidence: 99%
“…The metastable endo-Ni(Ph 2 PCH 2 CH 2 PPh 2 )Cl(ONO) was stable for 1 h when the crystal was kept in the dark at 100 K, and variable temperature studies showed that Ni(Ph 2 PCH 2 CH 2 PPh 2 )Cl(ONO) was stable at temperatures up to 160 K. At temperatures higher than 160 K, the nitrito ligand reverted to its nitro binding mode. [54], as shown in Figure 4. The benefits of LED over LASER irradiation are three-fold: first, LEDs are cheaper and readily commercially available in a range of wavelengths; secondly, LEDs have minimal radiative heating effects on the sample, which may result in the decomposition of the metastable state; and finally, LEDs have lower light intensity than LASERs, which gives greater control over the rate of photoactivation while reducing the risk of crystal damage from the high-intensity light.…”
Section: Photocrystallographymentioning
confidence: 84%
“…Beamline 11.3.1 uses a system of LEDs fitted into an aluminium ring as the source of UV, visible, or IR light [54], as shown in Figure 4. The benefits of LED over LASER irradiation are three-fold: first, LEDs are cheaper and readily commercially available in a range of wavelengths; secondly, LEDs have minimal radiative heating effects on the sample, which may result in the decomposition of the metastable state; and finally, LEDs have lower light intensity than LASERs, which gives greater control over the rate of photoactivation while reducing the risk of crystal damage from the high-intensity light.…”
Section: Photocrystallographymentioning
confidence: 99%